Inhibition of Ectopic Arginine Vasopressin Production by Phenytoin in the Small Cell Lung Cancer Cell Line Lu-165 - Ohta, Takahiro; Mita, Mitsuo; Hishinuma, Shigeru; Ishii-Nozawa, Reiko; Takahashi, Kazuhisa; Shoji, Masaru (Frontiers in Endocrinology, 2017)
Phenytoin, a voltage-gated sodium channel (Nav channel) antagonist, reportedly inhibits arginine vasopressin (AVP) release from an isolated rat neurohypophysis. So far, it is uncertain whether phenytoin has a direct action on ectopic AVP-producing neuroendocrine tumors. We studied the effect of phenytoin on the release of copeptin, the C-terminal fragment of pro-AVP, and expression of AVP gene in the human small cell lung cancer cell line Lu-165. Cells were maintained in RPMI1640 medium with 10% FBS and were used within the fifth passage. Copeptin was detected using a new sandwich immunoassay, and AVP mRNA levels were measured using real-time reverse transcription polymerase chain reaction. Treatment with phenytoin at a concentration of 25 μg/mL, but not at 5 or 10 μg/mL, had an inhibitory effect on copeptin levels in the medium at 48 h. At the same concentration, AVP mRNA levels in Lu-165 cells also decreased. Although a sodium challenge with added sodium at 20 mEq/L increased copeptin levels in the medium, a sodium challenge with added sodium at 10 mEq/L and at 20 mEq/L had no effect on AVP mRNA levels. Phenytoin at a concentration of 25 μg/mL suppressed copeptin levels in the medium under the sodium challenge with added sodium at 10 mEq/L and at 20 mEq/L. Phenytoin at a concentration of 25 μg/mL also decreased AVP mRNA levels in Lu-165 cells under the sodium challenge with added sodium at 10 mEq/L, but not at 20 mEq/L. Among five tested Nav channel subunits, Nav1.3 was highly expressed in Lu-165 cells. However, phenytoin significantly decreased Nav1.3 mRNA levels under the sodium challenge with added sodium at 10 mEq/L and at 20 mEq/L. These results suggest that Lu-165 cells are sensitive to phenytoin and sodium to control of AVP release and its gene expression. Phenytoin might have a direct action on ectopic AVP-producing tumors, suggesting the importance of Nav channels in AVP-producing neuroendocrine tumors.